Association of Severe Outcomes With Underlying Diseases Among Hospitalized COVID-19 Patients: A Retrospective Cohort Study - Pegah Mohaghegh; Mohammad Eslami; Farzane Ahmadi; Masoomeh Sofian; Rasool Karimi (International Journal of Epidemiologic Research, 2022)
Predicting the outcomes of coronavirus disease 2019 (COVID‐19) with comorbidities has been an interesting subject of study in the field of medicine. This study aimed to compare the clinical characteristics, radiologic features, and severe outcomes of COVID-19 among hospitalized COVID-19 patients with or without underlying comorbidity diseases. In this retrospective cohort study conducted from 1 June 2020 to 30 September 2020, 320 hospitalized cases with laboratory-confirmed COVID-19 and admitted to public hospitals in Arak, Iran, were examined. The mean ± SD age of the patients was 56.78 ± 20.06 years. The comorbidity group showed a substantially greater percentage of defined nodular pattern in chest X-ray (7.6% vs 2%, P = 0.024) and plural effusion in CT scan findings (9% vs 0%, P = 0.004). Intensive care unit (ICU) admission (6.9% vs. 0.6%, P = 0.003), mechanical ventilation (5.0% vs. 0.6%, P = 0.018), and death (6.3% vs. 0.0%, P = 0.002) were higher in the comorbidity group. Comorbidity group had a considerably greater ratio of ICU admission, invasive ventilation, and mortality.